Design optimization of active and passive structural control systems - Lagaros, Nikos D., 1970-; Plevris, Vagelis, 1976-; Mitropoulou, Chara Ch., 1983- (Information Science Reference, 2013)
"This book addresses the design optimization of active and passive control systems including earthquake engineering and tuned mass damper research topics and their link"-- Provided by publisher
Keywords: Structural control (Engineering); Structural optimization.; elektronické knihy; electronic books